2020
DOI: 10.1371/journal.pone.0238783
|View full text |Cite
|
Sign up to set email alerts
|

Chemical effects of diceCT staining protocols on fluid-preserved avian specimens

Abstract: Diffusible iodine-based contrast-enhanced computed tomography (diceCT) techniques allow visualization of soft tissues of fluid-preserved specimens in three dimensions without dissection or histology. Two popular diceCT stains, iodine-potassium iodide (I 2 KI) dissolved in water and elemental iodine (I 2) dissolved in 100% ethanol (EtOH), yield striking results. Despite the widespread use of these stains in clinical and biological fields, the molecular mechanisms that result in color change and radiopacity attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Two explanations are possible for the material studied here: (1) the energy (keV) used during the nano‐CT scanning was not appropriate to detect the fine differences in calcium content between bone and calcified cartilage (i.e., the KeV was either too high or too low); (2) iodine‐ethanol somehow decreased the natural contrasts between the ECM of bone and calcified cartilage. Early et al, 2020 showed that bone demineralization occurs during I 2 E staining in extant specimens, but more data needs to be collected to test whether I 2 E can also demineralize fossil bone and calcified cartilage and whether this is a process that must be taken in consideration when trying to understand changes in contrasts for fossil tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two explanations are possible for the material studied here: (1) the energy (keV) used during the nano‐CT scanning was not appropriate to detect the fine differences in calcium content between bone and calcified cartilage (i.e., the KeV was either too high or too low); (2) iodine‐ethanol somehow decreased the natural contrasts between the ECM of bone and calcified cartilage. Early et al, 2020 showed that bone demineralization occurs during I 2 E staining in extant specimens, but more data needs to be collected to test whether I 2 E can also demineralize fossil bone and calcified cartilage and whether this is a process that must be taken in consideration when trying to understand changes in contrasts for fossil tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The last limitation concerns molecular tests. If molecular or chemical works need to be performed on the fossil after immersion into iodine, its contamination should be taken into consideration, as it will most likely interact with originally preserved molecules in a process that may be nonreversible (see Early et al, 2020). It is also possible that ethanol removes or destroys some fossilized biomolecules and that many of them might get lost into the staining solution.…”
Section: Limitations Of the Iodine-ethanol Staining Methods For Fossil Tissuesmentioning
confidence: 99%
See 3 more Smart Citations